In the Service of Continuity. Ethnoarchaeology in Serbia - Aleksandar Palavestra (Etnoantropološki Problemi, 2011)
Ethnoarchaeology as a sub-discipline of archaeology primarily entails survey and research of various aspects of contemporary societies, in order to enable archaeologists to understand the dynamic processes that have created in the past the phenomena we now recognize as archaeological material, i.e. archaeological record. Ethnoarchaeological studies in Serbia have been ill-fated, since almost all the roads leading towards this approach have been jammed by various conceptions of the idea of continuity. In the Serbian archaeology, continuity has been understood as continuation of direct Aegean and Greek influences, as a metaphysical continuity of spirit, inexplicable “idealtypical” continuity, national continuity, or as a transmission of cultural traditions. Common to all these paradigms is the understanding of continuity as a given, and the contemporaneous ethnographic material has been used solely as an illustration of the long life of certain cultural shapes. The true value of ethnoarchaeology as a way of overcoming the statics of the archaeological record and gaining insight into the dynamics of the past has never been realized.